Adult Niemann-Pick disease type C mimicking features of multiple sclerosis - Grau, Armin J.; Brandt, Tobias; Weisbrod, Matthias; Niethammer, Rainer; Forsting, Michael; Cantz, Michael; Vanier, Marie T.; Harzer, Klaus (Journal of neurology, neurosurgery, and psychiatry, 1997)
Niemann-Pick disease type C is a panethnic autosomal recessive neurovisceral storage disorder characterised by a unique error in cellular trafficking of exogenous cholesterol. The most typical phenotype is characterised by hepatosplenomegaly, vertical supranuclear ophthalmoplegia, progressive ataxia, dystonia, and dementia and manifests in late childhood. Adult onset Niemann-Pick disease type C often includes psychosis and dementia.1 2 We report an adult female patient with biochemically verified Niemann-Pick disease type C in whom the initial diagnosis of multiple sclerosis was questionable because of a persistent splenomegaly. - - The 33 year old woman was referred to the Psychiatry Department of the University of Heidelberg in December 1994. She complained of progressive difficulties with memory and concentration, increasing social isolation, and problems with daily activities. The patient was unsure about the onset of her problems but suggested that they had started after the birth of her daughter three years previously. History, family history, and the patient’s fetal and childhood development were unremarkable. Her parents are non-consanguineous. School performance was satisfactory initially but later her learning behaviour became erratic and she failed her examinations after 10 school years. She worked as a saleswoman and after giving birth she lived on social support. With time she no longer managed to educate …
Elektronische Reproduktion der Druck-Ausgabe 13. April 2016
Gesehen am 11.07.2024